2018
DOI: 10.1101/247429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small interfering RNAs based on huntingtin trinucleotide repeats are highly toxic to cancer cells

Abstract: Synopsis Bullet points• CAG and CUG trinucleotide repeat (TNR) derived siRNAs are super toxic to cancer cells.• Super toxic siRNA duplexes kill cancer cells via RNAi by targeting survival genes with sequence complementarity.• Super toxic siRNAs reduce tumor growth in a murine cancer model without affecting normal tissues. Synopsis blurbTrinucleotide repeat disorders like Huntington's disease show severe neurological pathologies, but are also characterised by reduced cancer susceptibility. siRNAs based on trinu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 46 publications
(78 reference statements)
3
13
0
Order By: Relevance
“…Our published data on reducing tumor growth in xenografted OC bearing mice by delivering toxic siRNAs without affecting normal tissues (22, 45) is consistent with a model in which high amounts of nontoxic miRNAs protect cells from 6mer Seed Tox. This, however, raises the question of why Pt-resistant cells, which apparently also express a higher amount of nontoxic miRNAs, are still susceptible to 6mer Seed Tox.…”
Section: Discussionsupporting
confidence: 86%
“…Our published data on reducing tumor growth in xenografted OC bearing mice by delivering toxic siRNAs without affecting normal tissues (22, 45) is consistent with a model in which high amounts of nontoxic miRNAs protect cells from 6mer Seed Tox. This, however, raises the question of why Pt-resistant cells, which apparently also express a higher amount of nontoxic miRNAs, are still susceptible to 6mer Seed Tox.…”
Section: Discussionsupporting
confidence: 86%
“…We now compare the potency of siGGCAGU to siGGGGGC, the seed of which is present among other miRNAs, in miR-1237-5p. Both siRNAs had a chemically modified passenger strand to prevent loading into the RISC (12,17). When transfected into the OC cell line HeyA8, both siRNAs strongly slowed down cell growth ( Fig.…”
Section: Sigggggc Is Highly Toxic To Multiple Cancer Cells and Prefermentioning
confidence: 99%
“…Epidemiological studies conducted in patients with trinucleotide repeat expansion showed a decreased incidence of cancer [ 91 ]. Two hypotheses have been suggested: one proposes the fact that CAG expansion may increase the production of ncRNA that promotes less cancer [ 92 , 93 ].…”
Section: Mechanisms Of Pathogenesis In Hdmentioning
confidence: 99%
“…On the other hand, it increases the expression of the P53 tumor suppressor factor inducing programmed cell death [ 92 , 93 ].…”
Section: Mechanisms Of Pathogenesis In Hdmentioning
confidence: 99%